Estimation of Groundwater Quality in Barsis Region, Al-Jabal Al-Akhdar- Libya (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
The aim of this study is to evaluate quality of groundwater in Barsis which lies of the east Benghazi about 50 Km along the coast road where groundwater is the main source of another population reliable to meet their needs. There are a number of medium depth wells ranges from 30 -80 meters, Samples were collected from four wells samples were chemically and microbial analyses, especially pH meter, the electrical conductivity, total dissolved salts, turbidity, total hardness, chlorides, sulfates, indigestion magnesium and calcium, nitrate, ammonia, sodium, potassium, copper and iron were estimated. The results showed that there were some elements exceed the limit according to WHO standard 2006 and specifications Libyan standards 2008.
Keywords: Barsis; groundwater; total dissolved; total hardness; specifications standards